Hepatectomy and liver regeneration: from experimental research to clinical application - Tralhão, JG (2017)
BACKGROUND: The mechanisms and kinetics of hepatic growth have continuously been investigated. This study concerns liver regeneration in animal and patients who underwent partial hepatectomy evaluated by the hepatic extraction fraction (HEF) calculated through radioisotopic methods. METHODS: Thirty normal Wistar rats were submitted to an 85% hepatectomy, and 95 patients with primary and secondary liver tumours were included. In animal study, the liver regeneration kinetics was assessed by HEF using 99mTc-mebrofenin, the ratio liver/bodyweight and by using bromodeoxyuridine deoxyribonucleic acid incorporation. In patient study, the liver regeneration was evaluated by calculation of HEF before surgery, 5 and 30 days after hepatectomy. RESULTS: In animal, we verified a positive correlation between HEF kinetics and liver/bodyweight ratio or hepatocyte proliferation evaluated by bromodeoxyuridine deoxyribonucleic acid staining after 85% hepatectomy. In the clinical arm, no statistical differences of the HEF before hepatectomy, 5 and 30 days after hepatectomy, were observed. CONCLUSIONS: Our results support the view that human liver regeneration commences early, is fast, non-anatomical and functionally complete 5 days after hepatectomy. The fast functional liver regeneration may have a high clinical impact particularly concerning the post-operative oncological therapeutic approaches.